The incorporation of different additives to the fruit wrappers to increase shelf-life of local mangoes - Tan, Teik Swan (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Mangoes are prone to develop postharvest spoilage during storage period. There are numerous factors contributing to spoilage such as temperature, humidity and fungal attack. In this research, chitin and CaCl2 had been employed as fruits additive material. Then, polyethylene bag and biodegradable garbage bag were selected as fruit wrapping materials. This research also has investigated the effect of hot water treatment to the shelf life of mangoes. The influence of altering different treatments in terms of weight loss percentage, pH value of the mango juice, Total Soluble Solid (TSS) of mango juice and ascorbic acid content of the mango was examined at the constant room temperature and relative humidity.